P-030 Intra-aneurysmal flow diversion assessment using peri-operative advanced imaging after flow diverting stent (FDS) placement: are 64 wires better than 48?. (22nd July 2019) - Cancelliere M, N; Nicholson, P; Mendes L, K; Orru, E; Krings, T; Mendes Pereira, V
Abstract : Background and Purpose: Flow diverter devices (FDS) are a true breakthrough in the treatment of neurovascular disease. FDS reduce intra-aneurysmal blood flow inducing progressive thrombosis in a great proportion of treated intracranial aneurysms (IAs). Most of the first generation FDS devices had 48 braided wires, however, next generation devices have 64 wires with better deployment systems. The purpose of this study was to compare intra-aneurysmal flow modifications and flow diversion efficacy between deployments of a newly designed 64-wire (Surpass Evolve; Stryker) and a 48-wire (Pipeline; Medtronic) FDS in various patient-specific silicone aneurysm models. Methods: In-vitro experimental set-up using circulating water system and 4 silicone models with internal carotid aneurysms were used. We assessed the intra-aneurysmal flow modification after stent deployment (Evolve vs. Pipeline) using a flow-analysis digital subtraction angiography (DSA) system (AneurysmFlow, Philips Healthcare). The application uses a 3D rotational angiogram (3DRA) and 60 frames/sec DSA runs before and after device deployment to calculate a Mean Aneurysm Flow Amplitude Ratio (MAFA-R). MAFA-R's are of interest in this experiment as this ratio has previously been shown to be a reliable independent predictor for intracranial aneurysm thrombosis (Pereira et al., 2012). A total of 8 devices were deployed in four different silicone models. For each experimental model, we randomly selected either a Pipeline or Evolve stent to deploy first, followed by removal and deployment of the other stent. Intra-aneurysmal flow calculations were performed before and after each stent deployment and compared using a paired t-test. A VasoCT was performed to confirm suitable stent apposition to the arterial wall. Results: Average MAFA-Ratio values calculated from pre- and post-stent placement were significantly lower after deployment of the 64-wire device (mean= 0.62±0.09) compared to the 48-wire device (0.71±0.06); p=<0.05. Conclusions: Our in-vitro results show that the 64 wire FDS (Evolve) had superior flow diversion effect compared to the 48 wire FDS (Pipeline), suggesting that 64-wires are superior to 48-wire designs for flow diversion efficacy. Disclosures: N. Cancelliere: None. P. Nicholson: None. K. Mendes: None. E. Orru: None. T. Krings: None. V. Mendes Pereira: 1; C; Philips Healthcare. 2; C; Stryker, Medtronic.